2019
DOI: 10.1002/ejoc.201900104
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Brønsted Acid‐Catalyzed Azidation of Benzhydrols and Carbohydrates

Abstract: Benzhydryl alcohols were converted into their corresponding diarylazidomethane analogues using azidotrimethylsilane (TMSN3) in the presence of a catalytic amount of a Brønsted acid HBF4·OEt2. The azidation reactions proceeded in high yields and demonstrated excellent functional group tolerance to electron‐donating and electron‐withdrawing substituents. In addition, a range of unprotected functional groups including amine, amide, aldehyde and alcohol were well‐tolerated. Furthermore, this methodology was succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Based on previous studies for related transformations from our lab, [36–37] the reaction is expected to proceed via an S N 1 mechanism as proposed in Scheme 1. Following the protonation of benzhydryl alcohol 1 , a benzhydrylium ion 2 is generated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies for related transformations from our lab, [36–37] the reaction is expected to proceed via an S N 1 mechanism as proposed in Scheme 1. Following the protonation of benzhydryl alcohol 1 , a benzhydrylium ion 2 is generated.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported methodologies for the Brønsted acid‐ catalyzed alkynylation of benzhydryl alcohols with alkynyltrifluoroborate salts using tetrafluoroboric acid diethyl ether complex (HBF 4 ⋅OEt 2 ) as a catalyst [35] . However, the necessity to use excess of a Brønsted acid and to prepare trifluoroborate salts prompted us to investigate organosilanes as nucleophiles Recently, we reported that the allylation [36] and azidation [37] of benzhydrols with allyltrimethylsilane and azidotrimethylsilane respectively have been achieved using substoichiometric amount of HBF 4 ⋅OEt 2 . Herein, we report a direct coupling between benzhydrols and alkynyltrimethylsilanes in the presence of inexpensive, commercially available catalyst HBF 4 (aq.…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting observation that may have wider implications for the mechanism of other Brønsted acid‐catalysed dehydrative substitution reactions performed in nitromethane solvent. Bolshan and co‐workers later described the azidation of both benzhydrol derivatives and protected carbohydrates with trimethylsilyl azide catalysed by HBF 4 ⋅OEt 2 [68] …”
Section: Dehydrative Alkylation Of Heteroatomsmentioning
confidence: 99%
“…Bolshan and co-workers later described the azidation of both benzhydrol derivatives andp rotected carbohydrates with trimethylsilyl azide catalysed by HBF 4 •OEt 2 . [68] In 2019, Chan and co-workers showed that electron-rich primary anilinesu ndergo selective N-alkylation in nitromethane with ar ange of secondary andt ertiaryb enzylic alcohols catalysed by BCF 4 (10 mol %). [9] Subsequently,M aji disclosed the BCF 4 (1 mol %) promoted dehydrative alkylation of secondary anilines with ar ange of electron-rich primary,s econdary or tertiary benzylic alcohols.…”
Section: Dehydrative Cànb Ond Formationmentioning
confidence: 99%
“…The gold-catalyzed direct amination of alcohols affords a powerful methodology to form carbon–nitrogen bonds. 7,8 The pioneering work by Campagne and co-workers discovered the amination of benzhydrols catalyzed by NaAuCl 4 ·2H 2 O in CH 2 Cl 2 . 9 While electron-poor amine nucleophiles such as 4-nitroaniline, tosylamide and carbamate were good coupling partners, 2-aminopyridine substrates were not suitable with this catalyst system.…”
Section: Introductionmentioning
confidence: 99%